A Review for Video Authentication and Integrity - Nazar, Rahma; Hasso, Shahd Abdulrhman (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
In daily life, digital video authentication is a crucial problem. Digital videos may be recorded or captured by many different devices, and these can all be sent through the internet and other unsecured means. Due to the advancement of video editing tools, there is an issue with the editing or changing of digital video without authorization. There are many different methods and techniques, which are suggested for overcoming these problems. Digital video is the fundamental of surveillance system. However, it is easy to be modified by threats that may decrease drastically the trust of surveillance system. The techniques used for video authentication by various authors are discussed in this study.